Oxidation of Ammonia in Fish Ponds to Nitrates Using Free and Immobilized Nitrifying Bacteria - Ibrahim Yusuf; Asmau Rabiu Gamawa; Musa Haruna (UMYU Journal of Microbiology Research)
In fish farming, ammonia stands out as detrimental toxicant, with the potential to significantly impede growth and even lead to fish mortality. The adverse effects of ammonia exposure in aquatic environments primarily stem from elevated concentrations of unionized ammonium (NH3), which can readily permeate gill membranes. This study aimed at assessing the capability of free and mobilized forms of nitrifying bacteria in converting ammonia to nitrates. Nitrifying bacteria were isolated from water samples, resulting in the identification of two Pseudomonas species and two Bacillus species. The Bacillus sp., designated with the isolate code, B4 which exhibited the ability to convert ammonia to both nitrite and nitrate while demonstrating resilience to high ammonia concentrations. When Pseudomonas sp. (C4) and Bacillus sp. (B4) were utilized, the total ammonia concentration was reduced from 2 mg/L to 1.4 mg/L and 1.3 mg/L, respectively. Moreover, the immobilized forms of Pseudomonas sp. C4 and Bacillus sp. B4 achieved a more substantial reduction (75%), lowering the total ammonia concentration from 2 mg/L to 0.5 mg/L within 5-days period. Both nitrifying bacteria not only exhibited ammonia removal capabilities but also demonstrated their proficiency in transforming ammonia into nitrate. Immobilization proved effective in enhancing microbial tolerance to high ammonia concentrations, ultimately leading to improved water quality and the preservation of aquatic animal health.